2004
DOI: 10.1111/j.1442-9993.2004.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and assessment of restoration of a rainforest remnant at Wingham Brush, NSW

Abstract: Wingham Brush is a 9-ha remnant of lowland subtropical rainforest, on mid-north coast New South Wales, Australia, with high floristic diversity (about 200 species, more than 70 endemic trees and 27 endemic vines). A history of disturbance, environmental mismanagement and flooding from the Manning River resulted in many exotic species vigorously invading the rainforest. By the late 1970s weeds blanketed large sections of the forest, preventing regeneration of native species and destroying the canopy . By 1978 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Reformation of the canopy has been shown to be an important milestone in forest recovery, allowing for the microclimate on the forest floor to stabilise, in turn improving conditions for the germination and survival of shade‐loving rainforest species (Harden et al . ). The canopy gaps of ungrazed assisted regeneration sites provide sunlight for opportunistic grasses and forbs and increase the likelihood of these in the seed bank (Paul et al .…”
Section: Discussionmentioning
confidence: 97%
“…Reformation of the canopy has been shown to be an important milestone in forest recovery, allowing for the microclimate on the forest floor to stabilise, in turn improving conditions for the germination and survival of shade‐loving rainforest species (Harden et al . ). The canopy gaps of ungrazed assisted regeneration sites provide sunlight for opportunistic grasses and forbs and increase the likelihood of these in the seed bank (Paul et al .…”
Section: Discussionmentioning
confidence: 97%
“…The importance of controlling smothering weeds and vines through manual weeding or herbicide application has been noted in restoration of many Australian rainforest sites (Goosem & Tucker 1995;Lamb et al 1997;Harden et al 2004). The removal of invasive weeds reduces competition for space, light, and nutrients, improving survival of planted seedlings (Harden et al 2004). -year period (2003-2005) at restoration sites planted in the Injipara rainforest fragment.…”
Section: Evaluation Of Restoration Protocolmentioning
confidence: 99%
“…Few tropical forest restoration projects have reported percent survival by site, year, or species (Elliott et al 2003;McDonald et al 2003;Harden et al 2004;Lamb et al 2005). McDonald et al (2003) reported average survival rates of 39 and 49% after 12 months and 21 and 20% after 42 months at ridge-top and valley-bottom locations, respectively, in a tropical montane forest of Jamaica.…”
Section: Seedling Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, change in microenvironment, particularly intensity of light penetration might suppress native species regeneration. Canopy branches may break due to the sheer weight of overtopping exotic vines (Harden and Fox 1988 ;Harden et al 2004 ). Some species like Mikania micrantha tend to form dense ground cover carpets, suppressing native fl ora.…”
Section: Invasive Vinesmentioning
confidence: 99%